2018
DOI: 10.1111/are.13839
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of reproductive exhaustion usingUlva clathratain Pacific white shrimpLitopenaeus vannamei(Boone, 1931) broodstock during commercial maturation

Abstract: Ulva clathrata meal (2%) was supplemented in a fresh maturation diet for Litopenaeus vannamei broodstock in a commercial larval facility and its effects on reproductive performance, histology and histochemistry of gonad, and biochemical composition of gonad, hepatopancreas, and muscle were analysed. Females that were given Ulva in the diet had reduced mortality compared to controls, with no differences in males. Females fed Ulva also had bigger oocytes but only those in late vitellogenesis (+7%, p < 0.01) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…In the anomura crab C. clibanarius, lipids are present from early vitellogenesis, as in L. santolla, and suggest an exogenous supplement (Varadarajan & Subramoniam, 1980). The increase of triglycerides and decrease of phospholipids during vitellogenesis and postvitelogénesis has been observed in Pacific white shrimp Litopenaeus vannamei (Corral-Rosales et al, 2018), by the same Sudan Black B stain, used in this study.…”
Section: Discussionsupporting
confidence: 64%
“…In the anomura crab C. clibanarius, lipids are present from early vitellogenesis, as in L. santolla, and suggest an exogenous supplement (Varadarajan & Subramoniam, 1980). The increase of triglycerides and decrease of phospholipids during vitellogenesis and postvitelogénesis has been observed in Pacific white shrimp Litopenaeus vannamei (Corral-Rosales et al, 2018), by the same Sudan Black B stain, used in this study.…”
Section: Discussionsupporting
confidence: 64%
“…The complete replacement of fresh feed with formulated diet for penaeid broodstock maturation remains a major challenge for researchers and hatchery operators. In penaeid shrimp, numerous studies were reported regarding the fortification of broodstock diets with bioactive lipids, nutrients and animal extracts in an attempt to duplicate the gonad maturation promoting effects using fresh diets (Chung et al, 2011; Corral‐Rosales, Cruz‐Suárez, et al, 2018; Corral‐Rosales, Palacios, et al, 2018; Huang et al, 2008; Nguyen et al, 2012; Paibulkichakul et al, 2008; Wouters et al, 2002). However, most of the earlier works were met with limited success.…”
Section: Discussionmentioning
confidence: 99%
“…Protein content of the two best maturation diets used in this study (i.e., 45% and 55%) was within the range of protein levels of combined fresh diets routinely used in hatcheries as well as artificial diets previously reported to be effective for P . indicus (Cahu et al, 1995) Penaeus stylirostris (Bray et al, 1990), Penaeus monodon (Marsden et al, 1997; Paibulkichakul et al, 2008) and Litopenaeus vannamei (Adloo et al, 2020; Corral‐Rosales, Cruz‐Suárez, et al, 2018; Corral‐Rosales, Palacios, et al, 2018; Naessens et al, 1997; Wouters et al, 2002). However, this range of protein inclusion is higher than the protein requirement reported for juvenile P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. santolla and byCorral-Rosales et al (2018) in Pacific white shrimp, L. vannamei. These authors used SBB staining for triglycerides and phospholipids and used digital image analysis to quantify blue and gray pixel shades, respectively, as described by Rodríguez-Jaramillo et al(2008).…”
mentioning
confidence: 99%